The Use of Mobile Application as a Media in Physics Learning - Nuryantini, Ade Yeti; Yudhiantara, Rully Agung (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This article aimed to investigate the use of  mobile application among physics teachers in terms of its use as a tool for physics experiment and  the obstacles faced by teachers. The  data were collected using a questionnaire consisted of 15 questions. The participants were physics teachers in SMP/MTs and SMA/MA (junior high schools and high schools) in West Java, Indonesia. The questionnaire was delivered through social media Whatsapp in a form of Google Form. The results showed that mobile application had not been widely used by the teachers as a tool for physics experiment. This condition occured because of  their limited knowledge in using mobile application as a tool for physics experiment. It is expected that the use of mobile application training will be a solution in updating ICT skills of physics teachers.